The design of inductive power transfer system for fish aquarium using class-E inverter and LCCL impedance matching - Shakir Saat; Yusmarnita Yusop; Siti Huzaimah Husin; Md Rabiul Awal; Ahmad Husni Mohd Shapri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Nowadays, the accessories in fish aquarium systems such as water pump, internal filter, and LED light are powered using cables. This will cause to safety issue such as tangled wire, and risk of electric shock. Therefore, this work aims to design a wireless power transfer system to power up the fish aquarium’ accessories wirelessly without require any physical connection between source and loads. To be more specific, inductive power transfer (IPT) is used instead of capacitive power transfer (CPT) due to high efficiency ability owned by IPT. Class-E inverter circuit is proposed in this paper to convert DC to AC at nearly 100% efficiency. The inverter provides a low switching loss which is important as the circuit operates at high frequency, 1 MHz operating frequency. Furthemore, LCCL impedance matching circuit is added into receiver part of the system to enhance the efficiency of overall circuit. The analyses were done based on the distance between the coils and the misalignment of the coils against the output power and efficiency. The developed prototype is supplied by 24 V DC and capable to deliver 5 W power. The overall efficiency of the prototype is 87.81%.